2011
DOI: 10.1111/j.1365-2834.2011.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting nurses’ well-being from job demands and resources: a cross-sectional study of emotional labour

Abstract: The results of the present study indicate that nurses' well-being can be predicted by job demands, resources and emotional labour. There is a need to address organizational support and training programmes to enhance job satisfaction and reduce emotional exhaustion among nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
130
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(145 citation statements)
references
References 54 publications
9
130
1
5
Order By: Relevance
“…found to be positively associated with job satisfaction and a sense of personal accomplishment [4,27,32,37,38]. The differences in the consequences of applying the surface and deep acting can be observed in the case of the most prevalent cost of emotional labor, namely emotional exhaustion.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…found to be positively associated with job satisfaction and a sense of personal accomplishment [4,27,32,37,38]. The differences in the consequences of applying the surface and deep acting can be observed in the case of the most prevalent cost of emotional labor, namely emotional exhaustion.…”
Section: Introductionmentioning
confidence: 88%
“…Secondly, the results of studies on Polish teachers provide more and more support for the importance of psycho-social factors in the development of burnout [16,25,26]. It has been shown that strained relationships with students and their parents as well as with supervisors and colleagues may be one of performed on a daily basis by nurses, police officers, retail sales, bank and hotel employees [4][5][6][7][8]. Recent research has also focused on teachers as "emotional laborers" [2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The MBI is a 22-item self-administered questionnaire that assesses the three components of the burnout syndrome, namely emotional exhaustion, depersonalization and reduced personal accomplishment. It has been extensively used amongst healthcare professionals and demonstrates good reliability and validity different cultural settings (Chou, Hecker, & Martin, 2012;Endler, Fuchs, & MessenhollStrehler, 2011;Endler, Fischer, & Mitsche, 2013;Gillespie, Kalliath, & O'Driscoll, 2000). Responses are collected on a 7-point Likert scale where 0 reflects a statement that the resident has never felt and 6 a statement that the resident feels every day.…”
Section: B Systems Theory Framework (Stf)mentioning
confidence: 99%
“…Among samples of nurses, surface acting was observed to be positively linked to burnout and negatively linked with job satisfaction. Deep acting showed weaker relationships with burnout and no associations with nurses' job satisfaction [38][39][40].…”
Section: Emotional Labor and Cognitive Control Deficitsmentioning
confidence: 99%